2021
DOI: 10.1097/j.jcrs.0000000000000457
|View full text |Cite
|
Sign up to set email alerts
|

Changing practice patterns in European cataract surgery as reflected in the European Registry of Quality Outcomes for Cataract and Refractive Surgery 2008 to 2017

Abstract: Purpose: To study practice patterns in European cataract surgery over a 10-year period. Setting: European clinics affiliated to the European Registry of Quality Outcomes for Cataract and Refractive Surgery (EUREQUO). Design: Registry cohort study. Methods: The EUREQUO contains preoperative, intraoperative, and postoperative parameters reported by surgeons in many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 17 publications
1
31
0
Order By: Relevance
“…Cataract surgery represents one of the most commonly performed procedures in the world ( Pascolini and Mariotti, 2012 ). Advancements in anesthesia and surgical techniques made it possible to perform most of the procedures for cataract extraction under topical anesthesia ( Pellegrini et al, 2020 ; Lundström et al, 2021 ). On the one hand, this achievement has greatly reduced operating times and side effects related with local or general anesthesia ( Giannaccare et al, 2021 ; Lundström et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cataract surgery represents one of the most commonly performed procedures in the world ( Pascolini and Mariotti, 2012 ). Advancements in anesthesia and surgical techniques made it possible to perform most of the procedures for cataract extraction under topical anesthesia ( Pellegrini et al, 2020 ; Lundström et al, 2021 ). On the one hand, this achievement has greatly reduced operating times and side effects related with local or general anesthesia ( Giannaccare et al, 2021 ; Lundström et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The impact of optical biometry on refractive outcomes after cataract surgery can be appreciated by observing the steadily increasing percentage of patients achieving within ±1.0 D or ±0.5 D of their target refraction in studies between 1992 and 2017 [ 10 , 11 , 20 , 21 , 22 , 23 , 24 ]. Between 1992 and 2006, studies showed that 72.3–87.0% of patients achieved a deviation from the target refraction of ±1.0 D [ 10 , 11 , 20 , 21 ], which increased to 89.6–97.3% between 2007 and 2017 [ 22 , 23 , 24 ].…”
Section: Refractive Outcomes Prior To the Advent Of Modern Optical Bi...mentioning
confidence: 99%
“…The National Eye Institute has established that the risk of cataracts increases with each decade of life, starting around the age of 40. Phacoemulsification with intraocular lens implantation surgery has been proven to be safe, with very few surgical complications, and very effective in terms of the predictability of refraction and visual outcomes [2,3]. However, optimal precision in the refractive outcome in cataract surgery depends on a precise preoperative assessment and attention to pre-existing ocular comorbidities [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Phacoemulsification with intraocular lens implantation surgery has been proven to be safe, with very few surgical complications, and very effective in terms of the predictability of refraction and visual outcomes [2,3]. However, optimal precision in the refractive outcome in cataract surgery depends on a precise preoperative assessment and attention to pre-existing ocular comorbidities [2][3][4]. The proportion of coexisting ocular comorbidities according to the European Registry of Quality Outcomes for Cataract and Refractive Surgery (EUREQUO) is high and ranges from 27 to 30% and should be taken into consideration while qualifying patients for cataract surgery [2].…”
Section: Introductionmentioning
confidence: 99%